Management of Recurrent Congenital Preauricular Fistula: A Case Report - Ermalinda Kurnia; Fiona Widyasari; Abla Ghanie; Mariance (HM Publisher, 2023)
Congenital preauricular fistula is a malformation of the six auditory hillocks during the development of the auricle when an imperfect fusion of the first arch tuberculum to other tuberculums occurs and generates a tract. The difficulty in the surgical treatment for preauricular fistulas is the high recurrence rate. Surgical techniques were developed and modified to reduce the recurrence rate. This study aimed to describe a recurrent preauricular fistula and its treatment. A 7-year-old patient came to the otorhinolaryngology clinic with complaints of recurrent swelling and discharge on the left preauricular region. Initially, there was only a small hole at the base of the left ear since birth. A thick white discharge appeared and disappeared for 3 months. The lesion was itchy, and the patient frequently scratched it so that the area around the hole became red, swollen, and painful. The patient had undergone surgery for the same complaint in 2016 with a simple fistulectomy. Oral antibiotics were given and planned for fistulectomy under general anesthesia. Evaluation until 3 months postoperatively showed good surgical wounds and non-recurrent infections. In conclusion, the supra-auricula approach had a significantly lower recurrence rate than the sinusectomy approach, and was recommended to make it the standard primary procedure for preauricular sinus excision besides its use in recurrent cases.